Thank you a lot. So far, I got this, but how can I calculate c23?
solve[{c23 == c13 + a13, c22 == c12 + a12, c21 == c11 + a11,
c33 == a23 + b23 + c23, c32 == a22 + b22 + c22,
c31 == a21 + b21 + c21, b23 == 2 a a13, b22 == 2 a a12,
b21 == 2 a a11, b33 == b (2 a23 + b23), b32 == b (2 a22 + b22),
b31 == b (2 a21 + b21), a33 == -b33/2, a32 == -b32/2,
a31 == -b31 t/2,
a11 == 0, 2 c a12 - a112/3 - 2 c11 == 0, d - a12/3 + c12 == 0,
2 e a21 + (e - f)b21 == 0,
2e a22 + (e - f)b22 - a212/3 - b21 - 2 c21 == 0,
2ea23 + (e - f)b23 - a22/3 - b22/2 - c22 == 0, gb21 == 0,
gb32 - a312/3 - b31 - 2c31 == 0,
g*b33 - h - a32/3 - b32/2 - c32 == 0}, {a11, a12, a13, a21, a22,
a23, a31, a32, a33, b21, b22, b23, b31, b32, b33, c11, c12, c13,
c21, c22, c23, c31, c32, c33}]
{{a11 -> 0, a12 -> 0, a13 -> -((d e - b d g - e h)/(2 a b f g)),
a21 -> 0, a22 -> 0,
a23 -> -((-d e + d f + b d g + e h - f h)/(2 b f g)), a31 -> 0,
a32 -> 0, a33 -> -((-d + h)/(2 g)), b21 -> 0, b22 -> 0,
b23 -> -((d e - b d g - e h)/(b f g)), b31 -> 0, b32 -> 0,
b33 -> -((d - h)/g), c11 -> 0, c12 -> -d,
c13 -> c23 - (-d e + b d g + e h)/(2 a b f g), c21 -> 0, c22 -> -d,
c31 -> 0, c32 -> -d,
c33 -> c23 - (d e + d f - b d g - e h - f h)/(2 b f g)}}